الضغوط النفسية وعلاقتها بالعنف في الوسط المدرسي لدى تلاميذ المرحلة الثانوية - بن عمار، مريم (جامعة الوادي university of eloued, 2018)
"ملخص الدراسة باللغة العربية هدفت هذه الدراسة الى التعرف على العلاقة القائمة بين الضغوط النفسية والعنف في الوسط المدرسي لدى تلاميذ المرحلة الثانوية، من أجل ذلك استعانت الباحثة بعينة عشوائية طبقية، وبلغت عينة الدراسة (50) تلميذا وتلميذة من جميع الأقسام (المستوى الأول، الثاني، والثالث ثانوي) من ثانوية شوية الجباري بقمار ولاية الوادي، وقد استخدم المنهج الوصفي ألارتباطي الذي يتناسب مع موضوع الدراسة، وتمثلت أدوات الدراسة في مقياس الضغوط النفسية وآخر خاص بالعنف في الوسط المدرسي، ومن الأساليب الإحصائية نذكر معامل الارتباط بيرسون واختبار "" ت "" لحساب الفروق بين الأفراد العينة، وقد تم التحقق من الصدق والثبات لكلتا الأداتين وتوصلت الدراسة إلى النتائج التالية: _ توجد علاقة ذات دلالة ارتباطيه بين الضغوط النفسية والعنف في الوسط المدرسي لدى تلاميذ المرحلة الثانوية. _ لا توجد فروق دالة إحصائيا بين درجات أفراد العينة على مقياس الضغوط النفسية تعزى لمتغير الجنس. _ لا توجد فروق دالة إحصائيا بين درجات أفراد العينة على مقياس الضغوط النفسية تعزى لمتغير التخصص. _ توجد فروق دالة إحصائيا بين درجات أفراد العينة على مقياس الضغوط النفسية تعزى لمتغير المستوى الدراسي. _ لا توجد فروق دالة إحصائيا بين درجات أفراد العينة على مقياس العنف في الوسط المدرسي تعزى لمتغير الجنس. _ لا توجد فروق دالة إحصائيا بين درجات أفراد العينة على مقياس العنف في الوسط المدرسي تعزى لمتغير التخصص. _ توجد فروق دالة إحصائيا بين درجات أفراد العينة على مقياس العنف في الوسط المدرسي تعزى لمتغير المستوى الدراسي. "ملخص الدراسة بالأجنبية Abstract: The purpose of this study, which identified the relationship between psychological stress and violence in the school environment among high school students, for that hired the research group random sample stratified and reached the study sample (50) students from all sections (Level I, II, III secondary) from the high school SHOUA ALـ JABARI with gmar state ELـoued , has been used as a descriptive approach Correlative that fits with the thème of the study, and consisted study tools in psychological stress scale and other special violence in the school environment and statistical methods recall and test ""t"" to calculate the differences between the sample Pearson correlation coefficient was verification of the validity and reliability of both the tools and the study found the following results: _ There are correlation significant correlation between psychological stress and violence in the school environment among high school students. _ There are no differences between the scores of the sample on the psychological stress scale due to the variable sex. _ There are no differences between the scores of the sample on the psychological stress scale due to the variable specialization. _ There are differences between the scores of respondents on the psychological stress scale attributed to the school level. _ There are no differences between the scores of respondents on violence in the school environment scale due to the variable sex. _ There are no differences between the scores of respondents on violence in the school environment scale due to the variable specialization. _ There are differences between the scores of respondents on violence in the school environment scale attributed to the school level.
دراسة ميدانية بثانوية شوية الجباري بقمار - بولاية الوادي
مذكرة ماستر في علوم التربية تخصص إرشاد وتوجيه
Keywords: الضغوط النفسية ،العنف ،العنف المدرسي; Stress psychologique, violence, violence à l'école; Psychological stress, violence, school violence